(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
A prospective observational study was conducted for three months at Monika Diabetes Centre, Erode, Tamil Nadu. A total of 115 patients diagnosed with Type 1 or Type 2 Diabetes Mellitus and receiving antidiabetic therapy were enrolled. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8). Baseline demographic, clinical, and adherence data were collected through patient interviews and medical records. Structured patient counselling focusing on disease awareness, medication use, lifestyle modifications, and adherence strategies was provided. Higher medication adherence was observed among patients with better educational status and regular follow-up practices. Counselling significantly improved patients’ knowledge regarding diabetes management and enhanced adherence to prescribed medications. Patients receiving regular follow-up demonstrated higher adherence scores compared to those with irregular follow-up. The findings indicate that pharmacist-led counselling positively influences treatment compliance and self-management behaviors.